2020
DOI: 10.5194/essd-12-3067-2020
|View full text |Cite
|
Sign up to set email alerts
|

A homogenized daily in situ PM<sub>2.5</sub> concentration dataset from the national air quality monitoring network in China

Abstract: Abstract. In situ PM2.5 concentration observations have long been used as critical data sources in haze-related studies. Due to the frequently occurring haze pollution events, China started to regularly monitor PM2.5 concentration nationwide from the newly established air quality monitoring network in 2013. Nevertheless, the acquisition of these invaluable air quality samples is challenging given the absence of a publicly available data download interface. In this study, we provided a homogenized in situ PM2.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Among them, ground measurements are the most accurate way to obtain ambient PM 2.5 concentrations. However, due to the installation and maintenance costs of ground networks, monitoring stations are usually sparse and unevenly distributed, with most of the stations located in urban areas. , Moreover, PM 2.5 ground networks in China were established in 2013, so prior data are unavailable. As an alternative, chemical transport models (CTMs) could provide complete-coverage simulations of PM 2.5 concentrations and could reproduce the spatial and temporal trends of PM 2.5 concentrations when using reasonable emission inventories. , However, biases still exist in the simulated absolute values of PM 2.5 due to uncertainties in emission inventories and the lack of certain physical and chemical processes in the model. Satellite-retrieved aerosol optical depth (AOD) data, which can reflect the aerosol abundance in the atmosphere, have the advantage of long-term records and a high resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ground measurements are the most accurate way to obtain ambient PM 2.5 concentrations. However, due to the installation and maintenance costs of ground networks, monitoring stations are usually sparse and unevenly distributed, with most of the stations located in urban areas. , Moreover, PM 2.5 ground networks in China were established in 2013, so prior data are unavailable. As an alternative, chemical transport models (CTMs) could provide complete-coverage simulations of PM 2.5 concentrations and could reproduce the spatial and temporal trends of PM 2.5 concentrations when using reasonable emission inventories. , However, biases still exist in the simulated absolute values of PM 2.5 due to uncertainties in emission inventories and the lack of certain physical and chemical processes in the model. Satellite-retrieved aerosol optical depth (AOD) data, which can reflect the aerosol abundance in the atmosphere, have the advantage of long-term records and a high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the installation and maintenance costs of ground networks, monitoring stations are usually sparse and unevenly distributed, with most of the stations located in urban areas. 11,12 Moreover, PM 2.5 ground networks in China were established in 2013, so prior data are unavailable. As an alternative, chemical transport models (CTMs) could provide complete-coverage simulations of PM 2.5 concentrations and could reproduce the spatial and temporal trends of PM 2.5 concentrations when using reasonable emission inventories.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the anthropogenic PM 10 and PM 2.5 emissions in China decreased by 38 and 35% in 2017 compared to 2010 PM levels, respectively; these reductions were mainly caused by the implementation of the Air Pollution Prevention and Control Action Plan in 2013 (Zheng et al ., 2018). Based on the homogenized data from the National Air Quality Monitoring Network of China, PM 2.5 concentrations across China decreased by 7.3% per year between 2015 and 2019 (Bai et al ., 2020). Similarly, PM 2.5 concentrations estimated from MODIS aerosol optical depth (AOD) data also revealed a downward trend in particulate concentrations between 2012 and 2017 in city clusters such as BTH, Yangtze River Delta (YRD; which includes Shanghai, Jiangsu, Zhejiang, and Anhui provinces), and Pearl River Delta (PRD; which includes Guangdong Province) (Xue et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The gauged air pollutant concentration data have been released online on an hourly basis by the China National Environmental Monitoring Centre since late 2013. For quality control, outliers were first detected and removed from each pollutant dataset by following the criteria used in our previous study (Bai et al, 2020a). The missing values were then reconstructed using the diurnal-cycle-constrained empirical orthogonal function (DCCEOF) method proposed in Bai et al (2020b).…”
Section: In Situ Aod and Air Quality Measurementsmentioning
confidence: 99%